COVID-19, Telecommuting, and (Virtual) Sickness Presenteeism: Working From Home While Ill During a Pandemic - Ruhle, Sascha Alexander; Schmoll, René (Frontiers in Psychology, 2021)
This study explores (virtual) sickness presenteeism in the context of the COVID-19 pandemic. Using qualitative data from 505 members of the German working population, it investigates how working from home, which rapidly increased because of the COVID-19 outbreak, is perceived with regards to the pandemic. The study explores how this development affects the decision to show absence or presence in case of illness. More than 1,300 responses to different open-end questions by presenteeists and non-presenteeists were analyzed. The findings suggest that many previously identified reasons for deciding for or against presenteeism are still applicable. However, noteworthy differences with regards to both telecommuting and the pandemic occurred. Virtual sickness presenteeism seems to be more strongly encouraged by the possibility to adjust working conditions at home and the COVID-19 has affected the perceptions of health at work. The study contributes to a more in-depth understanding of (virtual) sickness presenteeism during a global pandemic. Six propositions for future research are developed and the importance of context for the consequences of virtual sickness presenteeism is discussed.